Treatment of Unwanted Pigment - Chance, Elizabeth W. (Facial Plastic Surgery, 2014)
Disorders of skin pigmentation pose significant challenges to both patients and physicians, as they have the unfortunate duality of being both common and difficult to treat conditions. This article reviews the etiology, pathophysiology, clinical presentation, and treatment options for melasma and postinflammatory hyperpigmentation. A thorough understanding of the disease process itself, expected agent efficacy, risks, and benefits of various treatments is crucial while treating these complex conditions.
Keywords: solar lentigines; melasma; postinflammatory hyperpigmentation